CUSTOMER RELATIONSHIP MANAGEMENT SERVICES PATIENT BHAKTI WIRA TAMTAMA HOSPITAL (Information Technology and Telematics, 2015)
Abstract The hospital is an important part of the region. Because a vital role in society in this era of globalization many new hospital stands either private or government owned. This gives rise to the existence of competition in providing services to patients because of the good service and provide maximum satisfaction to the patient. RS. Bhakti Wira Tamtama Semarang is under the command of the Army. The hospital is still far behind compared to other hospitals in Semarang, especially in the field of information technology. There are still many complaints from patients and suggestions that are not conveyed about hospital services. This is the basis of the idea of making the patient care system based CRM. Hopefully with this system all complaints and feedback from the patient can be measured by hospitals to improve patient care. Keywords: patient care sistem, poling, CRM